Violence and the female imagination : Quebec's women writers re-frame gender in North American cultures - Gilbert, Paula Ruth (McGill-Queen's University Press, 2006)
In the past twenty years Quebec women writers, including Aline Chamberland, Claire Dé, Suzanne Jacob, and Hélène Rioux, have created female characters who are fascinated with bold sexual actions and language, cruelty, and violence, at times culminating in infanticide and serial killing. Paula Ruth Gilbert argues that these Quebec feminist writers are "re-framing" gender.